Omega-6:3 Ratio More Than Absolute Lipid Level in Diet Affects Associative Learning in Honey Bees - Arien, Yael; Dag, Arnon; Shafir, Sharoni (Frontiers in Psychology, 2018)
Floral pollen is a major source of honey bee nutrition that provides them with micro- and macro-nutrients, including proteins, fatty acids, vitamins and minerals. Different pollens vary in composition, including in the essential fatty acids, alpha-linolenic acid (omega-3) and linoleic acid (omega-6). Monocultures, prevalent in modern agriculture, may expose honey bee colonies to unbalanced omega-6:3 diets. The importance of omega-3 in the diet for adequate learning and cognitive function, with a focus on suitable omega-6:3 ratio, is well documented in mammals. We have recently shown, for the first time in invertebrates, the importance of omega-3 in diets for associative learning ability in honey bees. In the current work, we examine the effect of the absolute amount of omega-3 in diet compared to the omega-6:3 ratio on honey bee associative learning. We fed newly-emerged bees for one week on different artificial diets, which had lipid concentration of 1%, 2%, 4% or 8%, with omega-6:3 ratios of 0.3, 1, or 5 respectively. We then tested the bees in a proboscis-extension response olfactory conditioning assay. We found that both omega-6:3 ratio and total lipid concentration affected learning. The most detrimental diet for learning was that with a high omega-6:3 ratio of 5, regardless of the absolute amount of omega-3 in the diet. Bees fed an omega-6:3 ratio of 1, with 4% total lipid concentration achieved the best performance. Our results with honey bees are consistent with those find in mammals. Best cognitive performance is achieved by a diet that is sufficiently rich in essential fatty acids, but as long as the omega-6:3 ratio is not high.